EXPLORATION OF BATIK JAMBI ON LEARNING TRANSFORMATION GEOMETRY - retno andriyani; Rahman Rahman; Riana Irawati; Ejen Jenal Mutaqin; Nurdin Kamis (FKIP Universitas Muhammadiyah Tangerang, 2023)
Geometry Ability is one of the mathematical abilities that must be mastered by students, this is because geometry ability is one part of learning mathematics. However, the reality in the field in junior high school students, students have difficulty in learning transformation geometry, namely in the material of reflection, rotation, translation and dilatation. This difficulty of students is caused by students not understanding the coordinate points on the cartesian plane. The difficulty of students in determining cartesian coordinates has the effect that students cannot determine straight-line drawings based on straight-line equations. Another thing that causes students difficulty in understanding the geometry of transformation is that students' ability to think abstractly is still very low, students cannot describe concepts from mirroring, turnover, shifting and dilatation. The purpose of this study is to understand the geometry of trasnsformas through the exploration of Jambi batik. The research method used is descriptive qualitative, the result of the research obtained is that there is a concept of transformation geometry in Batik Motik Jambi so that it can be applied in mathematics learning